2003
DOI: 10.1038/sj.bjp.0705439
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of ligand–receptor interactions in transmembrane domain V of the α2A‐adrenoceptor

Abstract: 1 The structural determinants of catechol hydroxyl interactions with adrenergic receptors were examined using 12 a 2 -adrenergic agonists and a panel of mutated human a 2A -adrenoceptors. The a 2A Ser201 mutant had a Cys-Ser201 (position 5.43) amino-acid substitution, and a 2A Ser201Cys200 and a 2A Ser201Cys204 had Ser-Cys200 (5.42) and Ser-Cys204 (5.46) substitutions, respectively, in addition to the Cys-Ser201 substitution. 2 Automated docking methods were used to predict the receptor interactions of the lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…Radioligand binding experiments in cell membranes (in the presence of GTP to uncouple the receptors from G-proteins and thereby induce a low-affinity state) showed that all three constructs were virtually indistinguishable from wild-type ␣ 2A -adrenergic receptors regarding saturation binding with the antagonist [ 3 H]RX821002 and competition with the various full and partial agonists used in this study (Table 1). The obtained K D and K i values were similar to published data (Peltonen et al, 2003;Nikolaev et al, 2006). These data indicate that the tetracysteine motifs did not affect ligand binding by the receptors.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Radioligand binding experiments in cell membranes (in the presence of GTP to uncouple the receptors from G-proteins and thereby induce a low-affinity state) showed that all three constructs were virtually indistinguishable from wild-type ␣ 2A -adrenergic receptors regarding saturation binding with the antagonist [ 3 H]RX821002 and competition with the various full and partial agonists used in this study (Table 1). The obtained K D and K i values were similar to published data (Peltonen et al, 2003;Nikolaev et al, 2006). These data indicate that the tetracysteine motifs did not affect ligand binding by the receptors.…”
Section: Resultssupporting
confidence: 80%
“…This has been proposed for the M 1 muscarinic receptor (Allman et al, 2000), the herpesvirus 8-encoded CXC-chemokine receptor ORF74-HHV8 (Rosenkilde et al, 2006), and specifically for the ␣ 2A -adrenergic receptor (Marjamaki et al, 1999;Nyronen et al, 2001). TMV binds to the catechol OH groups via several serine residues in the ␣ 2A -and the ␤ 2 -adrenergic receptor (Peltonen et al, 2003;Xhaard et al, 2006). This is compatible with our observation that agonists lacking one of the catechol groups fail to induce FRET signals close to TMV (I3-C construct).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Grid was generated at the centroid of the active site residues consisting of residues D3.32 (α2a: Asp113, α2b: Asp92, α2c: Asp131), S5.42 (α2a: Ser200, α2b: Ser176, α2c: Ser214) S5.46 (α2a: Ser204, α2b: Ser180; α2c: Ser218) [18,20,53]. The grid box generated is of the dimensions-outer/ grid box: 30, 30, 30 and ligand centre box/inner box: 10, 10, 10.…”
Section: Dockingmentioning
confidence: 99%
“…That TM5 serines in the D4 receptor have not been studied was surprising given the interest in D4 receptor agonists as potential therapeutics, evidence that conserved TM5 serines in biogenic amine G protein-coupled receptors (GPCRs) are sites of interaction for their amine neurotransmitters, and the conserved TM5 serines in the D1, D2, and D3 subtypes of dopamine receptor are key sites of catecholamine agonist interaction (for review see Floresca and Schetz, 2004). In addition, the high affinity of norepinephrine for only the D4 subtype of dopamine receptor, when coupled with the knowledge that the endogenous function of noradrenergic receptors relies on key interactions between conserved TM5 serines and norepinephrine (Peltonen et al, 2003), suggests that norepinephrine's affinity and efficacy at the D4 receptors may also involve the conserved serines of TM5. From the viewpoint of drug design and the tailoring of ligand selectivity and function, it would also be very informative to identify whether the interactions of TM5 serines, which are presumed to be important for the interaction of dopamine by analogy to the D1, D2, and D3 dopamine receptors, are necessary for D4 receptor activation by selective agonists.…”
mentioning
confidence: 99%